Synthesis and Structure of 2D Cobalt(II)-tartrate Hydrate Coordination Polymers Crystallised from Aqueous Solution - Mohammad Misbah Khunur; Yuniar Ponco Prananto (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2018)
Cobalt(II)-tartrate hydrate coordination polymer is successfully crystallisedfrom aqueous solution at room temperature. Unlike previous methods, diammonium tartrate was used and reacted directly with an aqueous solution of cobalt(II). Single crystal X-ray and ATR-IR analyses were performed toward the synthesized crystal. The crystal structure displaysa (6,3) 2D sheet which then grow into a 3D hydrogen-bonded network. Tetra- and hexa-dentate dianionic tartaric ligands are observed in the crystal structure, in which the hexadentate ligand connects four different cobalt centres. This method is considered feasible, affordable, and simple for the production of functional polymeric cobalt(II)-tartrate hydrate.